(3TQM ehLR GHf GdfajSs - (3HQgGf GdOjf fajS Hf YhV Hf Mcje GdcQeGfis; (3Ydj Hf CHj GdMRe GdbQTj , YdGA GdOjf CHh GdMSf , GHf GdfajS,J (B687 (3g` s ((3EHQGgje Hf CHj GdbGSe s)
(3ChdgG (B:s
(3bGd GdTjN Hf CHj GdMRe GdbQTi GdeJWHH bO QJHJ gPG GdcJGH Ydi CQHYI afhf (B: (3GdJQJjH (B: (3hVY cd TF ai eQJHJg s
(3BNQgG (B:s
(3hHdZfi Cf bhekG GbJUQhG YdjgG hMOgG , aeGJhG ai BNQ GdCeQ s
(3GdfSNI HgG MhGTs
(3HChdgG JedjcGJ efgG eG jYhO Edi SfI (B1176(3g` hbO cJH GdeJf HGdMeQIs
(3hgj Yf fSNI cJHJ ai GdbSWfWjfI SfI (B894(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdWHs